Time Loop Lapbook Media on Unit Time Material for Third-Grade Elementary School Students - Dina Pratiwi Dwi Santi; Setiyani; Dewinne Triyani (Jurnal Pedagogi dan Pembelajaran, 2023)
The low learning outcomes of students' mathematics are due to teachers' less optimal use of learning media. So to overcome these problems, students need media that can support the process of learning mathematics. This study aimed to determine the feasibility of time loop lapbook media on time unit material for 3rd-grade elementary school students. This research belongs to the type of development research that was developed using the Bord and Gall model. The subjects involved in this study were six experts,  two material experts, two media experts, two language experts, and 20 grade 3 elementary school students. Data collection in the study was carried out using test methods, interviews, validation questionnaires, and practicality questionnaires, with research instruments in the form of media product validity questionnaire sheets by experts. The data obtained in the study were then analyzed using qualitative descriptive analysis techniques and combining quantitative data to revise the development of lapbook learning media products. The results of the research analysis showed that the validity of the lapbook media, which included media experts, material experts, and linguists stated that the time lap lapbook learning media obtained a score of 89.5%, which means that this lapbook learning media is very feasible to use in supporting the learning process, especially on material unit time class III elementary school. Then the results of practicality, which include aspects of ease of use, the time required, and ease of interpretation, obtain a score of 94%, which means that the learning media for the lapbook is very practical. Based on the results of the data analysis, the lapbook media is in the valid category and is very feasible to develop.